Canon EOS 60D digital field guide - Lowrie, Charlotte K. (Digital field guides., 2011)
No-fail formulas for getting great digital photos from your Canon 60D The Canon EOS 60D offers a newly designed, hi-res 18.0 megapixel sensor and full high-definition movie recording capability. This full-color guide gets you completely caught up with all the bells and whistles that accompany this new dSLR. The handy trim size allows you to take it with you wherever you go so you can frequently refer to the top-notch tips, tricks, and techniques for getting unique and memorable photos and handling problematic shooting situations. Practical examples take you beyond the basics of the functions o.